The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00253-015-6605-2
|View full text |Cite
|
Sign up to set email alerts
|

A jack-of-all-trades: 2-mercaptosuccinic acid

Abstract: 2-Mercaptosuccinic acid (MS) is an important and versatile substance for diverse fields of applications of which the most significant are surveyed in this article. Biological, chemical, and physical properties of MS as well as the knowledge of its synthesis and microbial degradation are illustrated. In addition, exemplary structural analogs of the organic sulfur compound are commented. The key application of MS in nanotechnology is discussed in detail with particular emphasis on quantum dots (nanocrystals) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 110 publications
1
5
0
Order By: Relevance
“…74 Microbial conversion of mercaptosuccinic acid, which is structurally similar to DMSA, but has only one –SH functional group, has been reported in the literature. 75 This supports the prediction made by the biodegradability model.…”
Section: Resultssupporting
confidence: 84%
“…74 Microbial conversion of mercaptosuccinic acid, which is structurally similar to DMSA, but has only one –SH functional group, has been reported in the literature. 75 This supports the prediction made by the biodegradability model.…”
Section: Resultssupporting
confidence: 84%
“…In this study, the baculovirus or E. coli expression system was used to express the extracellular domains of VZV membrane proteins. Considering gE is an essential and most abundant membrane protein, the baculovirus expression system was used to express the extracellular domain of gE (rgE) similar to the published article 28 41 . The results showed that the rgE antigen could elicit plenty of antibodies recognizing linear or conformational epitopes locate on native gE, and neutralizing mAbs used in this study were obtained from rgE immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…1B11 was identified as a gE mAb bound to gE residues 140–330, and 8H6 was identified as a ORF9 mAb bound to ORF9 residues 81–135. VZV gE is the major and most immunogenic membrane protein; some gE-specific mAbs have been obtained, and some epitopes had been identified 29 41 42 . The residues 140–330 of gE recognized by 1B11 partly cover the residues 1–134 and 101–161 of gE that were previously identified as immunodominant regions in published literature 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…it acts as reducing agent due to the two carboxylic groups and as it is a thiol derivative, it can be used as a capping agent in nanoparticle production [ 17 ]. Furthermore, MS forms metal chelates with different metal ions [ 18 , 19 ], and it can act as a mono-, bi- or tridentate ligand since it possesses a thiol group as well as two carboxylic groups [ 20 ].…”
Section: Introductionmentioning
confidence: 99%